Measuring the Constructs of an Islamic Human Development Model (I-Hdm) for Nigeria's Rural Community - Oladapo, I. A.; Ab Rahman, A. (Universiti Sains Islam Malaysia, 2024)
This paper seeks to validate the Islamic human development model (I-HDM) by providing empirical evidence on the interrelatedness of social justice and human rights (exogenous and the three contextalised factors of education, health, and income (endogenous) based on the Maqasid Shariah framework. Conventionally, human development is measured through education, income and health, however, other integral components of development such as social justice and human rights are not taken into consideration in this mainstream model. This paper employed quantitative research design and used a survey questionnaire to collect the data. The findings support the hypothesised model with the model fit, significant inter-factor relationship, and high overall internal consistency of 0.804. The findings further show that many people living in rural Nigeria are unaware of their social and economic rights and the government responsibility to fulfilling them.